2020
DOI: 10.3390/biom10020248
|View full text |Cite
|
Sign up to set email alerts
|

From Seabed to Bedside: A Review on Promising Marine Anticancer Compounds

Abstract: The marine environment represents an outstanding source of antitumoral compounds and, at the same time, remains highly unexplored. Organisms living in the sea synthesize a wide variety of chemicals used as defense mechanisms. Interestingly, a large number of these compounds exert excellent antitumoral properties and have been developed as promising anticancer drugs that have later been approved or are currently under validation in clinical trials. However, due to the high need for these compounds, new methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 198 publications
(249 reference statements)
0
25
0
1
Order By: Relevance
“…En este contexto, se llevó a cabo un estudio de quimiomodulación de la actividad antiinflamatoria y antitumoral de una quimioteca obtenida a partir de dos diterpenos: ácido ent-kaurénico y ácido Adicionalmente se exploran nuevas fuentes de productos naturales poco estudiadas hasta ese momento. En concreto, la biodiversidad de los ecosistemas marinos resulta ser una fuente natural inagotable en el descubrimiento de nuevos fármacos antitumorales (11,12). Extractos obtenidos de numerosos invertebrados marinos (tunicados, corales, esponjas…) permitieron el aislamiento y la obtención de diversos fármacos.…”
Section: Los Primeros 30 Años (1940-1970s): "Screening Fenotípico"unclassified
“…En este contexto, se llevó a cabo un estudio de quimiomodulación de la actividad antiinflamatoria y antitumoral de una quimioteca obtenida a partir de dos diterpenos: ácido ent-kaurénico y ácido Adicionalmente se exploran nuevas fuentes de productos naturales poco estudiadas hasta ese momento. En concreto, la biodiversidad de los ecosistemas marinos resulta ser una fuente natural inagotable en el descubrimiento de nuevos fármacos antitumorales (11,12). Extractos obtenidos de numerosos invertebrados marinos (tunicados, corales, esponjas…) permitieron el aislamiento y la obtención de diversos fármacos.…”
Section: Los Primeros 30 Años (1940-1970s): "Screening Fenotípico"unclassified
“…Among them, six are used in cancer therapy: Cytarabine (Ara-C), eribulin mesylate (E7389), trabectedin (ET-743), brentuximab vedotin (SGN-35), polatuzamab vedotin and aplidin [ 36 , 37 ]. In addition, many other compounds are currently under clinical investigations, between the Phase II and Phase III of clinical trials, with promising anticancer activities [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…This particularity has led to a constant description of bioactive metabolites from marine bacteria (Buijs et al, 2019;Puglisi et al, 2019). Marine compounds display high cytotoxicity; since the 1990s it was suggested that over 1% of the marine samples analyzed possesses antitumoral activity while the same is 0.2% of terrestrial samples (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%